Conditional and constitutive expression of a Tbx1-GFP fusion protein in mice - Freyer, Laina (BioMed Central, 2013)
BACKGROUND: Velo-cardio-facial syndrome/DiGeorge syndrome (VCFS/DGS) is caused by a 1.5-3 Mb microdeletion of chromosome 22q11.2, frequently referred to as 22q11.2 deletion syndrome (22q11DS). This region includes TBX1, a T-box transcription factor gene that contributes to the etiology of 22q11DS. The requirement for TBX1 in mammalian development is dosage-sensitive, such that loss-of-function (LOF) and gain-of-function (GOF) of TBX1 in both mice and humans results in disease relevant congenital malformations. RESULTS: To further gain insight into the role of Tbx1 in development, we have targeted the Rosa26 locus to generate a new GOF mouse model in which a Tbx1-GFP fusion protein is expressed conditionally using the Cre/LoxP system. Tbx1-GFP expression is driven by the endogenous Rosa26 promoter resulting in ectopic and persistent expression. Tbx1 is pivotal for proper ear and heart development; ectopic activation of Tbx1-GFP in the otic vesicle by Pax2-Cre and Foxg1-Cre represses neurogenesis and produces morphological defects of the inner ear. Overexpression of a single copy of Tbx1-GFP using Tbx1(Cre/+) was viable, while overexpression of both copies resulted in neonatal lethality with cardiac outflow tract defects. We have partially rescued inner ear and heart anomalies in Tbx1(Cre/-) null embryos by expression of Tbx1-GFP. CONCLUSIONS: We have generated a new mouse model to conditionally overexpress a GFP-tagged Tbx1 protein in vivo. This provides a useful tool to investigate in vivo direct downstream targets and protein binding partners of Tbx1.